Metalloporphyrin Encapsulated Zeolite Y for Efficient Photocatalysis - Muhd Nor, Nik Nur Izzatul Ikmal (Universiti Teknologi PETRONAS, 2016)
Encapsulation of Cu and Mn based Metalloporphyrin into the pores of ZeoliteY prepared by ship-in-a-bottle approach for photocatalytic degradation of Orange II dye at varying condition of pH (3, 5, 7), temperature (25 0C, 35 0C, 45 0C) and initial concentration (10,20,30 ppm). Synthesized materials will be characterized using UVVis Spectroscopy, Fourier Transform Infrared Spectroscopy (FTIR), SEM-EDX, BET and elemental CHNS analysis. Dye intensity will be tested by UV-VIS over time. Parameters such as pH, temperatures and initial concentration will be optimized along with the kinetic study for complete dye removal.